Enhanced Expression of CNTD2/CCNP Predicts Poor Prognosis in Bladder Cancer Based on the GSE13507 - Gong, Mancheng; Song, Erlin; Huang, Guiying; Ni, Wenjun; Dong, Wenjing; Yuan, Runqiang (Frontiers in Genetics, 2021)
Background: Bladder cancer is the second most common genitourinary tract malignancy in the world and does not have sufficient prognostic indicators. CNTD2 is one of atypical cyclins, which may be related to the cell cycle and even the development of cancers. Early studies have shown that CNTD2 is associated with many malignancies. However, the relationship between CNTD2 and bladder cancer has not been reported. Methods: In this study, we explored the different expression of CNTD2 between 411 bladder cancers and 19 normal bladder tissues base on TCGA data set. GSEA was used to identify CNTD2-related signaling pathways. We analyzed the associations of CNTD2 expression and bladder cancer progression and survival using GSE13507. Results: Compared with 19 cases of normal bladder tissue, CNTD2 gene was highly expressed in 411 cases of bladder cancer. The high expression of CNTD2 strongly correlated with grade (P < 0.0001), T classiﬁcation (P = 0.0001), N classiﬁcation (P = 0.00011), M classiﬁcation (P = 0.044), age (P = 0.027) and gender (P = 0.0012). Bladder cancer patients with high CNTD2 expression had shorter over survival (P < 0.001). Meanwhile, univariate and multivariate analysis indicated that high CNTD2 expression was an independent unfavorable prognostic factor for bladder cancer patients (P < 0.001, P < 0.001, respectively). Conclusions: The expression level of CNTD2 strongly correlated with bladder cancer progression, and high CNTD2 expression may be applied as an unfavorable biomarker in bladder cancer patients.